Rapid diagnosis of pulmonary tuberculosis and detection of drug resistance by combined simultaneous amplification testing and reverse dot blot. Issue 6 (14th November 2017) - Chen, Yiwen; Zhang, Lahong; Hong, Liquan; Luo, Xian; Chen, Juping; Tang, Leiming; Chen, Jiahuan; Liu, Xia; Chen, Zhaojun
Abstract : Aims: Making a correct and rapid diagnosis is essential for managing pulmonary tuberculosis (PTB), particularly multidrug-resistant tuberculosis. We aimed to evaluate the efficacy of the combination of simultaneous amplification testing (SAT) and reverse dot blot (RDB) for the rapid detection of Mycobacterium tuberculosis (MTB) and drug-resistant mutants in respiratory samples. Methods: 225 suspected PTB and 32 non-TB pulmonary disease samples were collected. All sputum samples were sent for acid-fast bacilli smear, SAT, culture and drug susceptibility testing (DST) by the BACTEC TM MGIT TM 960 system. 53 PTB samples were tested by both RDB and DNA sequencing to identify drug resistance genes and mutated sites. Results: The SAT positive rate (64.9%) was higher than the culture positive rate (55.1%), with a coincidence rate of 83.7%. The sensitivity and specificity of SAT for diagnosing PTB were 66.7% and 100%, respectively, while those for culture were 53.9% and 84.2%, respectively. RDB has high sensitivity and specificity in identifying drug resistance genes and mutated sites. The results of RDB correlated well with those of DST and DNA sequencing, with coincidence rates of 92.5% and 98.1%, respectively. Conclusions: The combination of SAT and RDB is promising for rapidly detecting PTB and monitoring drug resistance in clinical laboratories.